(untitled) (International Journal of Engineering Sciences & Management Research, 2018)
Electrical And Electronic components can get damaged due to any kind of voltage or current malfunction. In electrical connection, voltage transients contain a high risk of destroying any electronic device. The point of this project is to build multifunctional protection device which can recognize any kind of disturbance in the path from the main line to the load and switch the power source automatically within a short range of time If the error in the transmission system is acknowledged, the proper authority can take steps to fix it and it would nullify the risk of operating devices. The proposed device will monitor the continuous flow of voltage from the main supply and if the main supply has fluctuations such as overvoltage and under voltage occurs, phase angle is changed from the requirement, the device will trip and shut off the distribution.. A set of relays and magnetic contactors has been used here for tripping. The voltage, phase sequence and load side ratings are determined by the user authority. A short time delay is used to avoid fluctuation and get a stable supply. This idea can be stretched out in future by accommodating more features creating more focus on speed, reliability, security and sensitivity. Giving the maximum protection is the only motive of building this device.